Why Isn’t the Head Direction System Necessary for Direction? Lessons From the Lateral Mammillary Nuclei - Dillingham, Christopher M.; Vann, Seralynne D. (Frontiers in Neural Circuits, 2019)
Complex spatial representations in the hippocampal formation and related cortical areas require input from the head direction system. However, a recurrent finding is that behaviour apparently supported by these spatial representations does not appear to require input from generative head direction regions, i.e. lateral mammillary nuclei. Spatial tasks that tax direction discrimination should be particularly sensitive to the loss of head direction information, however, this has been repeatedly shown not to be the case. A further dissociation between electrophysiological properties of the head direction system and behaviour comes in the form of geometric-based navigation which is impaired following lesions to the head direction system, yet head direction cells are not normally guided by geometric cues. We explore this apparent mismatch between behavioural and electrophysiological studies and highlight future experiments that are needed to generate models that encompass both neurophysiological and behavioural findings.